Rituximab in steroid resistant nephrotic syndrome - Agomoni Chaki; Farhana Rahman; Jahanara Arju; Abdullah- Al Mamun; Tahmina Jesmin; Sayed Saimul Huque; Afroza Begum; Habibur Rahman; Goam Muin Uddin; Ranjit Ranjan Roy (Paediatrica Indonesiana, 2019)
Background Nephrotic syndrome (NS) is one of the most common glomerular disease in children, characterized by massive proteinuria, hypoalbuminemia, dyslipidemia and edema. Steroid-resistant nephrotic syndrome (SRNS) and steroid-dependent nephrotic syndrome (SDNS) present challenges in pharmaceutical management. Patient need several immunosuppressant for optimal control, each of which has significant side effect and difficult to get desired results. Rituximab (RTX) is a monoclonal antibody that targets B cells and has been shown to be effective for patients with SRNS and SDNS. Objective To see efficacy of RTX in pediatric patients with SRNS. Method This retrospective study took place in Pediatric Nephrology Department of Bangabandhu Sheikh Mujib Medical University from July 2017 to June 2019. Patients diagnosed with SRNS who were treated with RTX and followed up for 6 months were enrolled in this study. Primary endpoint was achievement of remission after rituximab infusion; secondary endpoint was relapse-free survival rate in 6 months period following rituximab infusion. Results Total 7 patients were recruited in this study. Among them 4 were male. Clinical and lab parameters of all patients before and after RTX were compared. Complete remission achieved in 4/7 patients, partial remission in 2/7 patients and no response in 1/7 patient. Mean number of relapse in 3 patients before RTX infusion was 3.67 (SD 0.57) and after 0.33 (SD 0.00) (P=0.038). Conclusion RTX is a biological agent that is effective and promising drug in children with SRNS. Rituximab is useful to induce and maintain remission.